2021
DOI: 10.1136/tobaccocontrol-2020-056385
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of cushioning of tobacco tax increases in large retailers in Australia

Abstract: BackgroundTobacco companies may attempt to minimise the impact of tobacco tax increases on consumers by gradually passing on the price rise over several months. This study examined whether there was evidence of large Australian tobacco retailers engaging in this practice (known as cushioning) over a period including both routine indexation and large annual tobacco excise increases.MethodsAdvertised prices of nine factory-made cigarette (FMC) and nine roll-your-own tobacco (RYO) products were recorded from two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Companies continue to impede and oppose evidence-based tobacco control policies in multiple countries (see online supplemental table). 59–76 PMI’s recent actions suggest it has maintained the stance outlined in 2014 well beyond announcing its smoke-free vision in 2016 6 60…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Companies continue to impede and oppose evidence-based tobacco control policies in multiple countries (see online supplemental table). 59–76 PMI’s recent actions suggest it has maintained the stance outlined in 2014 well beyond announcing its smoke-free vision in 2016 6 60…”
Section: Resultsmentioning
confidence: 99%
“…Companies continue to impede and oppose evidence-based tobacco control policies in multiple countries (see online supplemental table). [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] PMI's recent actions suggest it has maintained the stance outlined in 2014 well beyond announcing its smoke-free vision in 2016. 6 60 The New Zealand government recently released a draft action plan for its Smokefree 2025 goal that proposes a comprehensive range of tobacco control policy interventions.…”
Section: Special Communicationmentioning
confidence: 99%
“…Strategic timing of implementation of price increases, which cushion consumers from the full effects of tax increases by spreading them out over several months. 21…”
Section: What Next For Tobacco Tax Policy?mentioning
confidence: 99%
“…26 More recent work found tobacco companies protected the new value partition they had created by cushioning tobacco tax increases and passing these on incrementally over several months. 24 Because NZ now has among the highest tobacco prices of any country, tobacco companies have a strong incentive to undermine tobacco excise taxes (the 2021 price of a pack of 20 Marlboro cigarettes was NZ$36.90 (~US$25)). NZ requires tobacco companies to furnish annual data on the number of cigarettes released for each brand, variant and pack size, and RRPs.…”
Section: Original Researchmentioning
confidence: 99%
“…A post-implementation study in Australia, the first country to introduce plain packaging, found that prices displayed on price boards did not decrease post-plain packaging 22. Analyses of RRPs post-plain packaging also found these were higher in real terms (ie, increased beyond inflation) and continued to rise after plain packaging 23 24…”
Section: Introductionmentioning
confidence: 99%